2003
DOI: 10.1038/sj.leu.2403180
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FLIPLong and FLIPShort in bone marrow mononuclear and CD34+ cells in patients with myelodysplastic syndrome: correlation with apoptosis

Abstract: Several apoptosis-inducing systems, including Fas/Fas ligand and TNF-related apoptosis-inducing ligand (TRAIL) and its receptors, are upregulated in myelodysplastic syndrome (MDS). FLIP (FLICE (FAS-associated death-domain-like IL-1b-converting enzyme)-inhibitory protein)) was identified as an inhibitor of FAS and TRAIL signals. Here, we characterized FLIP Long (FLIP L ) and FLIP Short (FLIP S ) expression in bone marrow mononuclear cells (BMMNCs) and in CD34 þ cells of 29 MDS patients, and in 17 normal volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 36 publications
5
37
0
1
Order By: Relevance
“…In both studies, increased c-FLIP S protein expression correlated with decreased caspase-8 processing at the Fas-mediated death-inducing signaling complex (44,45). Other studies indicate a role for elevated c-FLIP S in the survival of various tumor cells, including human gastric cancers (55,56) and cells from patients with myelodysplastic syndrome (57). We propose an alternative mechanism of generating p27FLIP by further cleavage of p43FLIP.…”
Section: Discussionmentioning
confidence: 86%
“…In both studies, increased c-FLIP S protein expression correlated with decreased caspase-8 processing at the Fas-mediated death-inducing signaling complex (44,45). Other studies indicate a role for elevated c-FLIP S in the survival of various tumor cells, including human gastric cancers (55,56) and cells from patients with myelodysplastic syndrome (57). We propose an alternative mechanism of generating p27FLIP by further cleavage of p43FLIP.…”
Section: Discussionmentioning
confidence: 86%
“…12 Those studies also suggest that PYCARD activation is suppressed by FLIP, an antiapoptotic adaptor molecule, which we have previously shown to be dysregulated in patients with MDS. 2,39 A possible interaction between up-regulation of PYCARD and expression of FLIP in the present model is currently being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These technical aspects coupled to lower patient numbers may have accounted for the failure to detect a correlation between disease progression and NF-kB activation. [67][68][69] Indeed, the expression of proapoptotic proteins of the Bcl-2 family like Bak, Bad, and Bcl-X S has a favorable prognostic value in MDS, while the expression of antiapoptotic proteins like Bcl-2 and Bcl-X L is associated with unfavorable prognostic value, suggesting that apoptosis suppression could be implicated in the transformation of MDS to AML. 68 XIAP overexpression has also been implicated in apoptosis suppression and transformation of MDS to AML.…”
Section: Myelodysplastic Syndromesmentioning
confidence: 99%
“…Determination of mRNA levels for FLIP Long and FLIP Short in patient bone marrow cells in a further study revealed that the FLIP Long /FLIP Short ratio positively correlated with the levels of NF-kB activity, suggesting its implication in apoptosis suppression during progression of MDS to AML. 65,67 Acute myeloid leukemia AML represents a heterogenous group of clonal stem cell malignancies arising from so-called leukemic stem cells (LSC). [70][71][72] LSC give rise to leukemic myeloid blasts arrested at different 72 maturation steps.…”
Section: Myelodysplastic Syndromesmentioning
confidence: 99%